Front Cover: Development of a New Structural Class of Broadly Acting HCV Non‐Nucleoside Inhibitors Leading to the Discovery of MK‐8876 (ChemMedChem 17/2017). (13th September 2017) - McComas, Casey C.; Palani, Anandan; Chang, Wei; Holloway, M. Katharine; Lesburg, Charles A.; Li, Peng; Liverton, Nigel; Meinke, Peter T.; Olsen, David B.; Peng, Xuanjia; Soll, Richard M.; Ummat, Ajay; et al.
Abstract : The front cover picture shows the crystal structure of MK‐8876 bound to the hepatitis C virus (HCV) NS5B protein. The biaryl linkage at the 5‐position of the benzofuran acts as a bridge between the Palm I and Palm II binding sites, enabling MK‐8876 to interact with both sites simultaneously. MK‐8876 shows broad potency against a wide range of HCV genotypes and maintains that potency against clinically relevant mutants. More information can be found in the Full Paper by Casey C. McComas et al. on page 1436 in Issue 17, 2017 (DOI: 10.1002/cmdc.201700228 ).